German elections and what to expect for the European agenda - Sandra Parthie; Wolfgang Eichert (Institut der deutschen Wirtschaft (IW), 2017)
While the populist equivalents to the likes of Marine Le Pen's Front National or Geert Wilder's Dutch party are much less center-stage in the German elections, the outcome and thus the impact on the EU is still uncertain. However, all the probable coalitions will not overhaul the current German stance on European politics. But proposals to change the governance of the EU Economic and Monetary Union (EMU) are on the agenda of all parties, of course with very different emphasis.
Keywords: 330